2022
DOI: 10.3390/insects13080687
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Distribution of the Asian Longhorned Beetle, Anoplophora glabripennis (Coleoptera: Cerambycidae) and Its Natural Enemies in China

Abstract: The Asian longhorned beetle, Anoplophora glabripennis, is a forestry pest found worldwide. A. glabripennis causes serious harm because of the lack of natural enemies in the invaded areas. Dastarcus helophoroides and Dendrocopos major are important natural enemies of A. glabripennis. MaxEnt was used to simulate the distribution of D. helophoroides and D. major in China, and their suitable areas were superimposed to pinpoint which regions are potentially appropriate to release or establish natural enemy populati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 59 publications
0
15
1
Order By: Relevance
“…Whereas, E. corollae only be suitable in a small area in northern India, and its suitable area will decrease in future climatic conditions, which may increase the difficulty of using E. corollae for biological control of L. erysimi in India. Zhang et al (2022a) Predicting the distribution of the Asian Longhorned Beetle, Anoplophora glabripennis (Coleoptera: Cerambycidae) and its natural enemies in China. The results showed that the Northern China (e.g., Xinjiang, Gansu, and Inner Mongolia), where A. glabripennis causes more serious damage, is also a potential suitable area for Dastarcus helophoroides and Dastarcus major, which provides a potential strategy for the management of A. glabripennis.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, E. corollae only be suitable in a small area in northern India, and its suitable area will decrease in future climatic conditions, which may increase the difficulty of using E. corollae for biological control of L. erysimi in India. Zhang et al (2022a) Predicting the distribution of the Asian Longhorned Beetle, Anoplophora glabripennis (Coleoptera: Cerambycidae) and its natural enemies in China. The results showed that the Northern China (e.g., Xinjiang, Gansu, and Inner Mongolia), where A. glabripennis causes more serious damage, is also a potential suitable area for Dastarcus helophoroides and Dastarcus major, which provides a potential strategy for the management of A. glabripennis.…”
Section: Discussionmentioning
confidence: 99%
“…Although ALB is widely distributed in China, including 24 provinces (Wang, 2004), it is less frequently found in Anhui, Jiangxi, Hubei, Hunan, Shanghai, Guangdong, Guangxi, Yunnan, Guizhou, and other southern provinces of China (Liu, 2016). CLB is a serious pest in citrus orchards and shelterbelts of C. equisetifolia in southern China.…”
Section: Introductionmentioning
confidence: 99%
“…Salix matsudana and Ulmus pumila are common urban street trees of high ecological value in the city of Changchun, China (Zhang et al, 2015;Yang et al, 2022a). The Asian longhorned beetle (A. glabripennis) is a serious pest of S. matsudana and U. pumila (Haack et al, 2006;Hu et al, 2009;Faccoli and Favaro, 2016;Liu et al, 2016); it is native to China and Korea and is largely polyphagous on woody broadleaf trees (Wang, 2004;Haack et al, 2006;Van der Gaag and Loomans, 2014;Meng et al, 2015). The female adult mainly feeds on bark and branches to provide essential nutrition for laying eggs.…”
Section: Introductionmentioning
confidence: 99%